2006
DOI: 10.1136/oem.2005.020545
|View full text |Cite
|
Sign up to set email alerts
|

Does enhanced information exchange between social insurance physicians and occupational physicians improve patient work resumption? A controlled intervention study

Abstract: Background: Patient work resumption after sickness absence varies even among patients with similar pathologies and characteristics. Explanations remain uncertain. One newly investigated field is ''information asymmetry'', a situation in which critical information is not appropriately exchanged between stakeholders in disability management. It is hypothesised that information asymmetry between social insurance physicians and occupational physicians prolongs sickness absence. Objectives: To assess the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
0
22
0
3
Order By: Relevance
“…Deciding whether or not to request and use information of third parties may influence the assessment, and this is done to a very varied extent [ 62 , 67 , 68 ]. Davis et al [ 69 ] found that diagnostic uncertainty among GPs was associated with higher rates of investigation and follow-up.…”
Section: Applying the Conceptualisationmentioning
confidence: 99%
“…Deciding whether or not to request and use information of third parties may influence the assessment, and this is done to a very varied extent [ 62 , 67 , 68 ]. Davis et al [ 69 ] found that diagnostic uncertainty among GPs was associated with higher rates of investigation and follow-up.…”
Section: Applying the Conceptualisationmentioning
confidence: 99%
“…Alle Akteure des Rehabilitationsprozesses sind von der Dringlichkeit einer zeitnahen, reibungslosen Kommunikation und Kooperation überzeugt [7,21,24,29,33,35,[43][44]55]. Es existieren jedoch multiple Hinweise für eine unbefriedigende Kooperation und Kommunikation zwischen Rehabilitationskliniken und Betriebsärzten sowie für mangelnde Kenntnisse bei anderen Facharztrichtungen hinsichtlich betriebsärztlichen Aufgaben und Kompetenzen [8,9].…”
unclassified
“…This was congruent with several studies that attached importance to social insurance officers (36, 37). Individual health improvement of the insured workers might also be negatively affected by information exchange with social insurance physicians and occupational physicians (38), insurance underutilization (39), poor personal contact with social insurance officers and health care professionals (40), and low use of evidence-based medicine and clinical practice guidelines in insurance medicine (41). Another study showed that the interaction with the social insurance agency and health care could be considered as an important part of the rehabilitation process (42).…”
Section: Discussionmentioning
confidence: 99%